(untitled) (Journal of history, 2023)
The article describes the image of a dog in the folklore and mythology of the Kazakh people, its place in the economy and culture, and also compares it with the image of a dog in the cultural heritage of other Turkic peoples. In order to determine the position of the dog in the Eurasian steppe since ancient times, the article examines the burial of the dog in archaeological excavations, its place in folk mythology, appearances in folklore, the function and place of the dog. dog in the Kazakh culture of the second half of the 19th century. The purpose and objectives of the study are to study the function of a dog in the economy and culture of the Kazakh people through the burials of dogs preserved from the Middle Ages, as well as to compare the image of a dog in traditional Kazakh society in a later period in chronological order. Results. In the research work of P. Makovetsky, A.I. Notes left by Dobrosmyslov and Claude Levi-Strauss, S. Kondybay, A. Toyshanuly, A. Toktabay, F. Arslanova, M. Shagyrbaev and others. Focusing on research materials in the works of scientists, their features are described. On the topic under consideration, the results of archaeological excavations in Kazakhstan and the Eurasian steppes, mythological similarities among the Turkic peoples and the image of a dog in folklore samples are presented. In addition, the occurrence of semantic characteristics of the image of a dog in the traditions and lifestyle of the Kazakh people is taken into account. In the article, the authors show that the understanding of the sacred concepts associated with the horse, wolf, eagle and cattle, which occupy a special place in the traditional economy and worldview of the Kazakh people, arose from the type of economy and lifestyle of the Kazakhs. people have evolved over the centuries. The totem beliefs of the people, various natural phenomena and changes in culture show that the role of the Kazakh people was important not only for livestock, but also for the dog that guarded the livestock and the house. An examination of this is shown in the article using specific data and ethnographic literature on whole blood coverage. Conclusion. Given the chronological breadth of the article and changes in cultural usage, the position of the dog in the culture of the Kazakh people is described with various data, and it is said that it was often used for hunting, like an eagle and an eagle, and not at a cult level. In addition, it is noted that the functions and use of the dog in nomadic life still need to be studied. Keywords: traditional culture, greyhound, folklore, mythology, cattle breeding, totemism, cult, archaeological research, hunting, use of dogs in the household. Expression of gratitude. The article was made within the framework of the grant funding project of the Ministry of Science and Higher Education of the Republic of Kazakhstan on the topic “Ethnozooarchaeological study of the role of the wolf and dog in the ancient and modern cultures of Kazakhstan” ( individual registration number: АР 14869303).